Right hemisphere or valence hypothesis, or both? The processing of hybrid faces in the intact and callosotomized brain. (February 2015) - Prete, Giulia; Laeng, Bruno; Fabri, Mara; Foschi, Nicoletta; Tommasi, Luca
Abstract: The valence hypothesis and the right hemisphere hypothesis in emotion processing have been alternatively supported. To better disentangle the two accounts, we carried out two studies, presenting healthy participants and an anterior callosotomized patient with 'hybrid faces', stimuli created by superimposing the low spatial frequencies of an emotional face to the high spatial frequencies of the same face in a neutral expression. In both studies we asked participants to judge the friendliness level of stimuli, which is an indirect measure of the processing of emotional information, despite this remaining "invisible". In Experiment 1 we presented hybrid faces in a divided visual field paradigm using different tachistoscopic presentation times; in Experiment 2 we presented hybrid chimeric faces in canonical view and upside-down. In Experiments 3 and 4 we tested a callosotomized patient, with spared splenium, in similar paradigms as those used in Experiments 1 and 2. Results from Experiments 1 and 3 were consistent with the valence hypothesis, whereas results of Experiments 2 and 4 were consistent with the right hemisphere hypothesis. This study confirms that the low spatial frequencies of emotional faces influence the social judgments of observers, even when seen for 28 ms (Experiment 1), possibly by means of configural analysis (Experiment 2). The possible roles of the cortical and subcortical emotional routes in these tasks are discussed in the light of the results obtained in the callosotomized patient. We propose that the right hemisphere and the valence accounts are not mutually exclusive, at least in the case of subliminal emotion processing. Highlights: Emotional hybrid faces were presented in two different paradigms. Healthy participants and an anterior callosotomy patient (AP) were tested. In a lateralized tachistiscopic paradigm the results supported the valence hypothesis. In a chimeric faces paradigm the results supported the right hemisphere hypothesis. The results support the two hypotheses as complementary rather than mutually exclusive.